I am a Troll : Inside the Secret World of the BJP's Digital Army - Chaturvedi, Swati (Newdelhi : Juggernaut Books, 2016)
Social media in India is awash with right-wing trolls who incite online communal tension and abuse, and sexually harass journalists, opposition politicians and anyone who questions them. But who are they? Why do they do what they do? And how are they organized? In this explosive investigation conducted over two years and including interviews with top politicians, bureaucrats, marketeers and trolls, Swati Chaturvedi finally lifts the veil over this murky subject. Riveting, urgent and deeply shocking, I Am a Troll is an essential read.
Keywords: History; geography; General -- collective by localities